Development of an algorithm for constructing a model of light pollution at a location using high-resolution visible satellite images - D. Alexandr; K. Polina (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
This article proposes a mathematical model for determining the relative level of light pollution in the night sky at a selected point in the area and the influence of a specific urban infrastructure object on it based on visible high-resolution satellite images. Statistical characteristics of the relative influence on light pollution of specific local objects were determined at an experimental local site. This model allows us to assess the degree of light pollution and its impact on various ecosystems, as well as develop strategies to reduce the negative impact of artificial lighting on nature.